Mapping and characterizing N6-methyladenine in eukaryotic genomes using single-molecule real-time sequencing - Zhu, Shijia; Beaulaurier, John; Deikus, Gintaras; Wu, Tao P.; Strahl, Maya; Hao, Ziyang; Luo, Guanzheng; Gregory, James A.; Chess, Andrew; He, Chuan; Xiao, Andrew; Sebra, Robert; et al.

(untitled) (Genome Research, 2018)
N6-Methyladenine (m6dA) has been discovered as a novel form of DNA methylation prevalent in eukaryotes; however, methods for high-resolution mapping of m6dA events are still lacking. Single-molecule real-time (SMRT) sequencing has enabled the detection of m6dA events at single-nucleotide resolution in prokaryotic genomes, but its application to detecting m6dA in eukaryotic genomes has not been rigorously examined. Herein, we identified unique characteristics of eukaryotic m6dA methylomes that fundamentally differ from those of prokaryotes. Based on these differences, we describe the first approach for mapping m6dA events using SMRT sequencing specifically designed for the study of eukaryotic genomes and provide appropriate strategies for designing experiments and carrying out sequencing in future studies. We apply the novel approach to study two eukaryotic genomes. For green algae, we construct the first complete genome-wide map of m6dA at single-nucleotide and single-molecule resolution. For human lymphoblastoid cells (hLCLs), it was necessary to integrate SMRT sequencing data with independent sequencing data. The joint analyses suggest putative m6dA events are enriched in the promoters of young full-length LINE-1 elements (L1s), but call for validation by additional methods. These analyses demonstrate a general method for rigorous mapping and characterization of m6dA events in eukaryotic genomes.